Collaboration in Teacher Education
IX, 277 p.
Keywords: Change is an ongoing aspect of education and educators are always seeking alternative and effective approaches to it. The approaches, in the context of mathematics teacher education, discussed in this book are based on joint work between the individuals involved in the process. However, the factors that influence success within co-operative or collaborative change processes have not been the focus of scientific investigation. This book systematically investigates collaborative endeavours in a number of different domains of teacher education. The fifteen chapters in the four main sections of the book explore and reflect on a variety of issues related to collaborative mathematics teacher education practice and research - such as classroom coaching, mentoring or co-learning agreements - highlighting the evolution and implications of collaborative enterprises in different cultural settings. The resultant accounts should appeal to educational researchers, research students and practitioners around the world.